A European Map Regarding the Strictness of the Transfer Pricing Regulations - Ioana Ignat; Liliana Feleagă (Journal of Accounting and Management Information Systems (JAMIS), 2017)
In the context in which transfer pricing may represent a mechanism through which multinationals have the possibility to move funds internationally, in order to prevent the base erosion and profit shifting between multinationals, countries over the world have adopted various transfer pricing regulations. Furthermore, some of the countries adopted stricter regulations than others. The objective of our research was to identify the level of strictness for the transfer pricing regulations from the European countries. To achieve this objective, we analyzed the transfer pricing regulations of all European countries and we built a transfer pricing strictness index, based on which we defined 4 categories of countries (where category 1 includes the countries with the least strict transfer pricing regulations and category 4 countries with the strictest regulations). After that, we illustrated how these categories are distributed on the European map. In order to collect the information, we used the transfer pricing guides issued by the Big Four companies for the year 2015. The study`s results show that the strictness of the transfer pricing regulations decreases from the west of Europe to east. Moreover, most of the countries were included in category 2, respectively category 3, meaning that the transfer pricing regulations from the European continent are not so flexible, but in the same time are not so strict.
Keywords: M48; K34; F23; 650; transfer pricing; strictness; regulations; map; Europe